Community action and the environment . - Lovering, Matthew; McAuliffe, Mark (Video Education Australasia, 2003)
In 1996 residents living in Werribee learned that a toxic waste dump was being proposed for a nearby quarry site owned by CSR. This program explores the action taken by the community in their conflict with the state government and the company. A localcommunity group, "WRATD" - Werribee Residents against Toxic Dumps - became the main driving force successfully opposing the toxic waste dump